2019
DOI: 10.1029/2019gl084601
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Dynamic Contributions to Summer 2018 Anomalous Weather Over Europe

Abstract: Summer 2018 was one of the driest and hottest experienced over northwestern Europe. In contrast, over southern Europe, it was marked by cooler and wetter conditions with flooding over Greece and Spain. This contrasting pattern was particularly enhanced over a 3‐week period starting on 21 June. Two atmospheric patterns are thought to have largely contributed to this anomalous weather: the positive North Atlantic Oscillation (NAO+) and a Wave‐7 pattern. Using linear regressions on detrended data, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 27 publications
5
53
0
Order By: Relevance
“…This long‐lasting blocking has found to be related to the quasi‐stationary Rossby waves, transients, and large‐scale modes on different time scale (Dole et al, ). Before the 2018 heatwave, a stripped high‐pressure system formed over northern Europe in late June, which was produced by the combination of the positive phase of the North Atlantic Oscillation and the Rossby wave‐7 pattern (Drouard et al, ; Kornhuber et al, ). As a low‐pressure system over the North Atlantic gradually moved south, squeezing the high‐pressure system, and finally forming a blocking over northwest Europe (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This long‐lasting blocking has found to be related to the quasi‐stationary Rossby waves, transients, and large‐scale modes on different time scale (Dole et al, ). Before the 2018 heatwave, a stripped high‐pressure system formed over northern Europe in late June, which was produced by the combination of the positive phase of the North Atlantic Oscillation and the Rossby wave‐7 pattern (Drouard et al, ; Kornhuber et al, ). As a low‐pressure system over the North Atlantic gradually moved south, squeezing the high‐pressure system, and finally forming a blocking over northwest Europe (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have explored the potential attributions of this strong heatwave. The positive North Atlantic Oscillation and stationary Rossby wave‐7 pattern were suggested to be responsible for the 2018 European heatwave (Drouard et al, ; Kornhuber et al, ). In addition, Vogel et al () argued that this extreme event could not have occurred without anthropogenic climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The NH2018 event was characterized by a hemisphere-wide wavenumber 7 circulation pattern, which was also observed during the European heat waves of 2003, 2006(Kornhuber et al, 2019b. A strong positive mode of the North Atlantic Oscillation contributed significantly to the extreme summer conditions in Europe by amplifying the weather anomalies induced by the wavenumber 7 pattern (Drouard et al, 2019). An analysis of simulations from the 5th phase of the Coupled Model Intercomparison Project (CMIP5, Taylor et al, 2012) showed that the total area affected by hot extremes during the NH2018 event, despite being unprecedented in the historical record, was actually consistent with the present-day level of global warming (Vogel et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…During late June and the first weeks of July 2018 an exceptionally strong and persistent Rossby wavenumber 7 pattern dominated the weather in the Northern Hemisphere (Drouard et al, 2019;Kornhuber et al, 2019b). The wave pattern was associated with simultaneous extreme events across the entire hemisphere including heat waves in the western United States, eastern Canada, western Asia and large areas in Europe (Kornhuber et al, 2019b;NOAA, 2018;Vogel et al, 2019).…”
Section: Storylines For the Nh2018 Eventmentioning
confidence: 99%
See 1 more Smart Citation